1987
DOI: 10.1007/bf02370682
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium population genetics: Effect of clover variety and inoculum dilution on the genetic diversity sampled from natural populations

Abstract: Strains of Rh&obium leguminosarum biovar trifolii were isolated from nodules formed on white clover plants (Trifolium repens) following inoculation with soil suspensions, and examined for allozyme variation.A similar spectrum of genetic variants was recovered from each of four different clover cultivars, and over a 104-fold range of soil dilutions. The frequency of allozyme variants was not significantly affected by the choice of cultivar or dilution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…If we had sampled loci that were more polymorphic, it is possible that we would have picked up differences in frequency reflecting site or host effects. There are some reports of differences in preference among T. repens cultivars (Russell and Jones, 1975; Roughley et al ., 1976; Jones and Hardarson, 1979), but in other cases there was little effect (Roughley et al ., 1976; Harrison et al ., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…If we had sampled loci that were more polymorphic, it is possible that we would have picked up differences in frequency reflecting site or host effects. There are some reports of differences in preference among T. repens cultivars (Russell and Jones, 1975; Roughley et al ., 1976; Jones and Hardarson, 1979), but in other cases there was little effect (Roughley et al ., 1976; Harrison et al ., 1987).…”
Section: Discussionmentioning
confidence: 99%
“…All isolates were examined by PAGE of three enzymes (Young, 1985;Harrison et al, 1987) : glucose-6-phosphate dehydrogenase (G6PD), superoxide dismutase (SOD) and P-galactosidase (BGAL). The alleles of each locus were labelled alphabetically with a single letter in order of descending PAGE mobility.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous studies of agricultural systems, sym plasmid transfer was determined from the correlation between major genotypes at nodulation and nonsymbiotic loci. Both host plant species (23,28,35) and sampling location (36,37) are considered important in shaping genetic divergence of Rhizobium, so we used the unique strategy of sampling nodules of the same legume species across several sites to distinguish the effects of host plant and sampling location on the divergence of Rhizobium plasmid and chromosomal loci. In contrast to previous studies, we observed a strict correlation between genetic groups at symbiotic plasmid and chromosomal loci across several sampling locations and host plant species, which strongly argues for a surprising stability of sym plasmids within chromosomal lineages of native Rhizobium populations.…”
mentioning
confidence: 99%